Bad unicorn / 1 - Clark, Platte F. (Bad Unicorn Trilogy, 2014)
Max Spencer is an underachiever but when a carnivorous unicorn, Princess the Destroyer, and an evil wizard, Rezormoor, bring him, the only one who can read the legendary Codex of Infinite Knowability, to their magical realm, he must find the courage to save himself, his friends, and the entire human race.